Fabrication and characterization of thin-film field-effect transistors with alkyl-phenyl[n]phenacenes (n = 4–6). Issue 43 (29th September 2022) - Zhang, Yanting; Eguchi, Ritsuko; Okamoto, Hideki; Goto, Kenta; Tani, Fumito; Yamaji, Minoru; Goto, Hidenori; Kubozono, Yoshihiro
Abstract : 3-Decyl-10-phenyl[5]phenacene (PhC10-PIC) molecule shows good FET characteristics in case of using ZrO2 gate dielectric, owing to strong fastener effect and large π-overlap. Abstract : Alkyl-phenyl[ n ]phenacenes ( n = 4–6) are newly synthesized molecules, in which two types of alkyl substituents, decyl and tetradecyl groups, are added to the benzene core frameworks, [ n ]phenacenes. These include: 2-decyl-8-phenyl[4]phenacene (PhC10-CHR), 3-tetradecyl-8-phenyl[4]phenacene (PhC14-CHR), 3-decyl-10-phenyl[5]phenacene (PhC10-PIC), 3-tetradecyl-10-phenyl[5]phenacene (PhC14-PIC), 2-decyl-10-phenyl[6]phenacene (PhC10-FUL), and 2-tetradecyl-10-phenyl[6]phenacene (PhC14-FUL). [4]phenacene, [5]phenacene, and [6]phenacene are named "chrycene, " "picene, " and "fulminene, " respectively. In this study, field-effect transistors (FETs) using thin films of the above molecules were fabricated with SiO2 and ZrO2 gate dielectrics, and their p -channel transport properties were fully investigated to clarify whether these molecules are available for FET devices. Among these molecules, the PhC10-PIC thin-film FET with ZrO2 provides a higher field-effect mobility ( μ ) compared with other molecules, which can reach up to 1.66 cm 2 V −1 s −1 . This paper discusses a design strategy for phenacene-type molecules for high-performance thin-film FET.